2014
DOI: 10.1098/rsta.2012.0438
|View full text |Cite
|
Sign up to set email alerts
|

Control of ferroelectricity and magnetism in multi-ferroic BiFeO 3 by epitaxial strain

Abstract: Recently, strain engineering has been shown to be a powerful and flexible means of tailoring the properties of ABO 3 perovskite thin films. The effect of epitaxial strain on the structure of the perovskite unit cell can induce a host of interesting effects, these arising from either polar cation shifts or rotation of the oxygen octahedra, or both. In the multiferroic perovskite bismuth ferrite (BiFeO 3 -BFO), both degrees of freedom exist, and thus a complex behaviour may be expected as one plays with epitaxia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…It is hard to model such a system as not only the desired orientation effect but also a completely different morphology applies for certain films and not for others (Pitfall 3). Complete coverage and nearly ideal interfaces have been obtained for other routes [76][77][78]. Concurrently, the introduction of dislocations has been found to play a large role at outer interfaces of ferroelectrics [76].…”
Section: Sample Preparation: Realistic Materials Morphologies and Implmentioning
confidence: 76%
See 1 more Smart Citation
“…It is hard to model such a system as not only the desired orientation effect but also a completely different morphology applies for certain films and not for others (Pitfall 3). Complete coverage and nearly ideal interfaces have been obtained for other routes [76][77][78]. Concurrently, the introduction of dislocations has been found to play a large role at outer interfaces of ferroelectrics [76].…”
Section: Sample Preparation: Realistic Materials Morphologies and Implmentioning
confidence: 76%
“…Another method to introduce stress transformation from one phase to another can be performed by material engineering through epitaxial growth of two different crystals with a lattice mismatch of up to 5% [76,78]. Inducing a strain by a corresponding field related to a certain material will evoke stress in the other phase thus tuning the material properties of the non active phase [101].…”
Section: Strain Measurement At the Micron-scale And Interfacesmentioning
confidence: 99%
“…These results are presented in the supplementary materials. We note that previous studies have shown that the magnetic structure of these materials is very sensitive to strain, growth direction, and synthesis conditions 28,29 .…”
mentioning
confidence: 69%
“…First-principles calculations [36] even predict that by simply depositing the room-temperature FM double perovskites Bi 2 NiReO 6 and Bi 2 MnReO 6 on a substrate strain should turn their antipolar bulk ground state into a FE one. For the materials already showing bulk FE, strain engineering has also been shown to be a powerful and flexible means of tailoring the properties of ABO 3 thin films [37,38] or superlattices [39]. The effect of epitaxial strain on the structure of the perovskite unit cell can induce a host of interesting effects, arising from either polar cation shifts or rotation of the oxygen octahedra, or both.…”
Section: Introductionmentioning
confidence: 98%